Consistency in acceleration patterns of football players with different skill levels - Arpinar-Avsar, P.; Ruhi Soylu, A. (Journal of Sports Science & Medicine, 2010)
The aims of the present study were to compare the consistency in the lower limb acceleration patterns during inside and instep kicks performed by players with different skill levels, and to investigate the correlation between subjective rating scores for skill level relative to their kicking performance and knee acceleration repeatability. Thirteen club-level male soccer players of ages between 15-16 years participated in this study. Skill levels of individual players were quantified previously by evaluating shooting performance as a numerical value ranging from 1 to 10. Further evaluations were held through tri-axial acceleration data recorded at proximal tibial tuberosity beneath each patella on the players' knees, in a procedure in which players were asked to complete four randomly ordered shooting trials of inside and instep kicks with 2-minute resting intervals. Hence, the mainstream data used in consistency calculations are in the form 4 by 1200 matrices (acceleration vs. time) per subject. In order to evaluate the consistency of acceleration data, the mean of the standard deviations (mSD) were calculated, and the associated Pearson-r correlation coefficients were incorporated to obtain mSD vs. skill correlations. As a result, repeatability was found to increase with skill level at z-axis acceleration for instep kicks only. However, it is possible to find the most appropriate orientation (for the two kicks) for meaningful correlations using vector rotations on the 3 orthogonal acceleration data, and this study shows that, after such suitable vector rotations, positive repeatability results could also be acquired for the inside kicks.